Infants With Congenital Adrenal Hyperplasia Are at Risk for Hypercalcemia, Hypercalciuria, and Nephrocalcinosis - Schoelwer, Melissa J. (J Endocr Soc, 2017)
CONTEXT: Hypercalcemia is reported as a rare finding in adrenal insufficiency, but is not well described in congenital adrenal hyperplasia (CAH). METHODS: A retrospective chart review was conducted of patients with CAH diagnosed before the age of 2 years who had at least one recorded serum calcium measurement. Data from birth to 6 years of age were reviewed. RESULTS: Of the 40 patients who met inclusion criteria, 33 (82.5%) had at least one elevated calcium concentration and 21 (53%) had two or more elevated calcium concentrations. Of the 126 elevated serum calcium concentrations, the median was 10.9 mg/dL (range, 10.6 to 14.2 mg/dL). Median age at the last elevated calcium measurement was 5 months (range, 0.3 to 46 months). Serum calcium concentration was inversely related to age (r = −0.124; P = 0.004). Overall, calcium level positively correlated with 17-hydroxyprogesterone (17OHP) concentration (r = 0.170; P = 0.003), and this remained significant after adjusting for age (P < 0.05). However, patients had hypercalcemia with both high and low 17OHP concentrations. Serum calcium concentration also was positively related to glucocorticoid (r = 0.196; P = 0.012) and fludrocortisone (r = 0.229; P = 0.003) doses, and remained significant after age adjustment. Only seven patients were evaluated for hypercalciuria. Of these, six had at least one period of documented hypercalciuria. Three patients had nephrocalcinosis on renal ultrasound. CONCLUSION: Children with CAH are at risk for developing hypercalcemia, hypercalciuria, and nephrocalcinosis. Further studies are needed to determine the broader prevalence and the etiology of hypercalcemia in CAH.